Physical and chemical parameters of saffron and use as a color in Greek yogurt flavored with passion fruit jelly (Research, Society and Development, 2020)
The objective was to evaluate the physical and chemical parameters of saffron rhizomes and flours, determine the best method of drying saffron rhizomes, evaluate the best flour in relation to antioxidant activity and percentage of phenolic compounds, as well as to analyze acceptability and intention purchase of Greek yogurt added with natural saffron coloring and passion fruit jelly. The rhizomes of Cúrcuma longa L, were sanitized, sanitized, and analyzed for length, width, weight and color, then they were processed and transformed into flour. The flours were subjected to color analysis, scanning electron microscopy, antioxidant activity and total phenolic compounds. The flours were subjected to three types of drying, in sun, oven and microwave. The total phenolic content of saffron flours was higher in sun-dried and microwave-dried samples. The flour used as a dye in Greek yogurt was saffron flour dried in microwaves due to the better result of antioxidant activity. It was concluded that the most suitable method for drying the rhizomes was the greenhouse method, in relation to the antioxidant activity, it was the microwave method. Greek yogurt flavored with passion fruit and saffron jelly obtained good acceptability, so it was found that the substitution of synthetic dyes with natural dyes did not negatively affect its flavor.